Pharmacological analysis of the role of kisspeptin-10 in reinforcing mechanisms - Sarng S. Pyurveev; Andrei A. Lebedev; Eugeny R. Bychkov; Petr D. Shabanov (Research Results in Pharmacology)
Introduction: Behavioral and substance addictions are driven by shared neurobiological mechanisms, often involving the reward system. Kisspeptin-10, a neuropeptide primarily linked to reproductive functions, has emerged as a potential modulator of reward-related behaviors and decision-making. This study explores the effects of kisspeptin-10 on impulsivity, compulsivity, and reinforcement mechanisms.